Теоретичні та прикладні питання здійснення судового контролю слідчим суддею у кримінальному провадженні - Жупанова, О. О.; Zhupanova, O. O.; Юхно, О. О.; Yukhno, O. O.; Олександр Юхно (Право і безпека. – 2017. – № 4 (67). – С.100-105, 2017)
Розглянуто наукові та прикладні питання здійснення судового контролю через процесуальну діяльність слідчого судді щодо забезпечення прав, свобод і законних інтересів у кримінальному провадженні його учасників. Проаналізовано чинне законодавство та його недосконалість, понятійний апарат і наукові позиції з досліджених питань. Проаналізовано і співвіднесено прокурорський та судовий контроль, висвітлено особливості судового контролю, що здійснює слідчий суддя.

The legislative, scientific and applied issues of realizing judicial control through the procedural activity of an investigating judge concerning the provision of rights, freedoms and legitimate interests in the criminal proceedings of its participants have been considered. The authors have carried out the analysis of the conceptual apparatus on the researched issues in the criminal procedure and related branches of law, scientific positions of scholars about its application in science and in practice. The correlation of concepts, practice and peculiarities of the application of prosecutor, judicial, controlling and supervisory control on the basis of previous and current criminal procedural legislation of Ukraine has been analyzed. The authors of the article have also analyzed the novels of the current criminal procedural legislation that regulates the implementation of judicial control in general and by the investigating judge in criminal proceedings in particular. The authors have established certain features of such activity and existing gaps, inconsistencies and differences of its legal regulation; have provided propositions and recommendations for the improvement of the current legislation, in particular the Criminal Procedure Code of Ukraine. It has been emphasized that there is no generalization of the practice of higher courts in relation to such activity, which adversely affects the further development of research and enforcement practice in this area. The authors has separately assessed the amendments in the legislation of Ukraine adopted in October and November 2017, which will come into force in January 2018, regarding an investigating judge in the criminal proceedings, has established significant differences, inaccuracies, inconsistencies. It has been stressed that indicated novels will not contribute to the proper execution of the tasks of criminal proceedings in accordance with the Art. 2 of the Criminal Procedural Code of Ukraine and do not correspond to the possibilities of their implementation in the courts, based on the number of investigating judges who carry out expanded powers, in particular, they exercise judicial control in criminal proceedings in order to ensure the rights, freedoms and legitimate interests of participants in criminal proceedings.

Рассмотрены научные и прикладные вопросы осуществления судебного контроля через процессуальную деятельность следственного судьи по обеспечению прав, свобод и законных интересов в уголовном производстве его участников. Проанализированы действующее законодательство и его несовершенство, понятийный аппарат и научные позиции по исследованным вопросам. Проанализированы и соотнесены прокурорский и судебный контроль, освещены особенности судебного контроля, который осуществляет следственный судья.
Theoretical and applied issues of realizing judicial control by an investigating judge in the criminal proceeding
Теоретические и прикладные вопросы осуществления судебного контроля следственным судьёй в уголовном производстве
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; контроль; прокурорський контроль; судовий контроль; нагляд; слідчий суддя; права і свободи; кримінальне провадження; суб’єкти кримінального процесу; учасники провадження; прокурорский контроль; судебный контроль; надзор; следственный судья; права и свободы; уголовное производство; субъекты уголовного процесса; участники производства; control; prosecutor’s control; judicial control; supervision; investigating judge; rights and freedoms; criminal proceedings; subjects; participants in proceedings